มายาคติในการสื่อสารออนไลน์ของเว็บไซต์การพนัน - ชูผกา, สุระชัย (Journal of Business, Innovation and Sustainability (JBIS), 2016)
มายาคติในการสื่อสารออนไลน์ในเว็บไซต์การพนันมุ่งเผยให้เห็นถึงรูปแบบความสัมพันธ์การสื่อสารสัญญะกับมายาคติและอุดมการณ์ต่างๆ ที่แอบแฝงอยู่เบื้องหลังในประเทศไทย โดยวิธีการอภิปรายความและการถอดรื้อโครงสร้างความหมาย ภายใต้แนวคิด มายาคติของโรล็องค์ บาร์ตส์,การเข้ารหัสและถอดรหัสาร ของ สจ๊อวต์ ฮอลล์ และโลกเสมือนและสภาวะเหนือจริง ของ ฌอง โบดริยารด์ การศึกษาได้เก็บรวบรวมข้อมูลจากรูปแบบการนำเสนอของเว็บไซต์การพนันเว็บไซต์ที่ได้รับความนิยมสูงสุด 3 อันดับแรก และรวมรวบข้อมูลเพื่อการสัมภาษณ์จากผู้ที่เปิดรับเว็บไซต์พนัน 12 กรณี ผลการวิจัยพบว่า เว็บไซต์พนันออนไลน์สามารถยุบสัญลักษณ์ ภาพตัวแทน และตัวบ่งชี้ต่างในสังคมประกอบสร้างจนสามารถเปลี่ยนภาพลักษณ์ของการพนันกลายเป็นภาพมายาแห่งเกมที่เร้าใจจนเกิดสภาวะเหนือจริงครอบงำความคิดและจินตนาการแห่งความสุข ความเหนือกว่า และความเหมือนเป็นธรรมดาภายใต้การล้อมรัดของรูปแบบและลีลาการนำเสนอของเว็บไซต์พนันที่มีความสอดคล้องกับอุดมการณ์ทุนนิยม อุดมการณ์เชิงชนชั้น อุดมการณ์ประชาธิปไตยเสียงข้างมาก และอุดมการณ์อินเตอร์เน็ต ผลดังกล่าวทำให้เว็บไซต์พนันออนไลน์กลายเป็นบ่อนพนันในโลกเสมือนที่ทำให้ความหมายในทางสังคมของคำว่า การพนันแปรเปลี่ยนไหลลื่นแตกต่างออกไปจากบ่อนการพนันในโลกความเป็นจริงและส่งผลให้ผู้เปิดรับเว็บไซต์พนันออนไลน์เกิดความต้องการเล่นพนันออนไลน์ได้อย่างไม่รู้จบและไม่รู้สึกว่าการพนันออนไลน์เป็นเรื่องผิดกฎหมายผิดศีลธรรม ภาครัฐจึงควรเร่งหาหนทางปราบปรามและป้องกัน The Myth of Online Communication in Gambling Websites The research entitled The Myth of Online Communication in Gambling Websites aimed at studying the relationship between the sign’s construction of the gambling websites under such ideological domination as myth within the audience’s perception. The research methodology embraced an intertextual analysis for reality’s deconstruction. The study, supported by Ramkhamheng University, synthesized three theoretical perspectives to be the conceptual framework namely Mythologies, the Encoding Model of Communication, and the Simulation concept. The research collected relevant data and information from the top four gambling websites, ranked by Google, along with in-depth interviews of 12 receivers of the access of website exposures. The study found that the websites mixed various signs, symbols, and indexes from realistic and fantastic worlds for the reconstruction of a gambling reality. The sites were more attractive than real casinos in the audience’s mind due to the image of infinite real-time, unlimited happiness, and high credibility. Although all kinds of gambling are illegal and prohibited in the Thai society, the receivers recognized the online gambling as an excited game without any negative feeling. They enjoyed gambling with the sense of control and trustfulness over the hyper-reality of the game. This simulation stemmed from the merger of the sign consumption and the ideological dominance through the myth of maximization in capitalism, extortion in class struggle, majority rule in democracy, and freedom of value in the internet world. Therefore, the research recommended that media’s mobilization for anti-online gambling campaign and online media literacy must be created to prevent millions of Thais from gambling addiction. DOI: http://dx.doi.org/10.14456/becj.2015.17